2006
DOI: 10.1089/hum.2006.17.167
|View full text |Cite
|
Sign up to set email alerts
|

Adenoviral Vector-Delivered Pigment Epithelium-Derived Factor for Neovascular Age-Related Macular Degeneration: Results of a Phase I Clinical Trial

Abstract: Twenty-eight patients with advanced neovascular age-related macular degeneration (AMD) were given a single intravitreous injection of an E1-, partial E3-, E4-deleted adenoviral vector expressing human pigment epithelium- derived factor (AdPEDF.11). Doses ranging from 10(6) to 10(9.5) particle units (PU) were investigated. There were no serious adverse events related to AdPEDF.11 and no dose-limiting toxicities. Signs of mild, transient intraocular inflammation occurred in 25% of patients, but there was no seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
139
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 315 publications
(142 citation statements)
references
References 10 publications
2
139
0
1
Order By: Relevance
“…To meet such treatment modality, in 2006, Campochiaro and colleagues delivered the gene encoding PEDF to the retina of nvAMD patients using adenoviral (Ad) delivery and reported significant improvement in 25% of patients after 12 weeks and no harmful side effects 7, 8. However, no follow-up to the trial has been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To meet such treatment modality, in 2006, Campochiaro and colleagues delivered the gene encoding PEDF to the retina of nvAMD patients using adenoviral (Ad) delivery and reported significant improvement in 25% of patients after 12 weeks and no harmful side effects 7, 8. However, no follow-up to the trial has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, three additional gene therapy clinical trials are ongoing (https://clinicaltrials.gov/): trial NCT01494805 is based on the use of an adeno-associated viral (AAV) vector encoding sFlt-1, a splice variant of VEGF receptor 1; trials NCT01301443 and NCT01678872 are based on the use of a lentiviral vector expressing endostatin and angiostatin (RetinoStat). Aside from the results reported by Campochiaro et al., 8 the only other available data are from two Association for Research in Vision and Ophthalmology abstracts in 2014 and 2016 (M. Davies et al., 2014, Invest. Ophthalmol.…”
Section: Introductionmentioning
confidence: 99%
“…A phase I study has been conducted to evaluate the safety and tolerability of a single intravitreal injection of an adenoviral vector expressing the anti-angiogenic cytokine pigment epithelium-derived factor (PEDF). 2 In this multicentre dose-escalation trial that involved 28 patients, a single intravitreal injection of adenoviral vector (E1-, partial E3-, E4-deleted) was generally well tolerated. Signs of mild-to-moderate transient intraocular inflammation were reported in 25% of patients but no dose-limiting toxicities or serious adverse events attributed to the study drug were identified.…”
mentioning
confidence: 98%
“…The results of experimental studies have led to the development of a phase I clinical trial of adenovirus-mediated PEDF expression by intravitreal vector delivery in individuals with neovascular AMD. 97 Patients in this trial developed treatable inflammatory responses following vector administration, and only the group of patients receiving the highest dose of virus showed some improvements in outcome measures, such as neovascular lesion size. 97 To maximize the treatment potential of PEDF, a vector, such as AAV, that does not elicit immune responses would be better suited to delivering long-term, stable treatment effects.…”
Section: Vector-mediated Neuroprotection and Modulation Of Ocular Angmentioning
confidence: 88%